Corporate ownership structure and the informativeness of accounting earnings in East Asia - Fan, Joseph P.H; Wong, T.J (Journal of Accounting and Economics, 2002)
This study examines the relations between earnings informativeness, measured by the earnings–return relation, and the ownership structure of 977 companies in seven East Asian economies. Our results are consistent with two complementary explanations. First, concentrated ownership and the associated pyramidal and cross-holding structures create agency conflicts between controlling owners and outside investors. Consequently, controlling owners are perceived to report accounting information for self-interested purposes, causing the reported earnings to lose credibility to outside investors. Second, concentrated ownership is associated with low earnings informativeness as ownership concentration prevents leakage of proprietary information about the firms’ rent-seeking activities.